Antimicrobial Activities of Three Commercial Essential Oils Derived from Plants Belonging to Family Pinaceae - Truchan, Mariola; Tkachenko, Halyna; Buyun, Lyudmyla; Kurhaluk, Natalia; Góralczyk, Anna; Tomin, Vładimir; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The aim of this study was to compare the antibacterial effects of several essential oils derived from plants belonging to family Pinaceae and subfamily Abietoideae (cedar oil, fir oils derived from Silver fir Abies alba and Siberian fir Abies sibirica, respectively) against some Gram-positive and Gram-negative bacteria. The Kirby–Bauer disk diffusion test for measuring zone diameters of bacterial growth inhibition was used. The fir oil derived from Silver fir Abies alba showed considerably more profound activity than the cedar oil and fir oil derived from Siberian fir Abies sibirica. Maximum antibacterial activity was shown by essential oil of silver fir oil against Escherichia coli, methicillin-sensitive Staphylococcus aureus (MSSA), and Pseudomonas aeruginosa. Silver fir essential oil was found to be active against K. pneumoniae while Siberian fir essential oil showed the mild activity of clear inhibition zone against P. aeruginosa and methicillin-sensitive Staphylococcus aureus. Silver fir essential oil has the highest antibacterial potential from all tested essential oils and could be a promising candidate concerning possible applicability in the prevention of bacterial growth. Moreover, essential oils may play an important role in the discovery of new drugs for the treatment of a wide range of pathogenic microorganisms in the near future.